THE IMPLEMENTATION OF VIDEO IN TEACHING LISTENING - Astri Nur Utari; Vina Nurviyani (Universitas Suryakancana, 2018)
ABSTRACT According to Meyer (2002) in Muniandy and Veloo (2011:173; cited in Tugiwati, 2014) defines video as a kind of multimedia material consisting of verbal and non-verbal presentations displaying simultaneous images, narration and on screen text. Video is an electronic device that produces live images with a sounds. The major goals of this study were to investigate the implementing of video in teaching listening, the object of this study is the second grade students in senior high school. This study employed a classroom action research. Classroom action research on this study was conducted in two cycles. There are four steps in each cycle; planning, action, observation, and reflections. The data of this study were analyzed by using mix method, both of quantitative and qualitative. For quantitative method, the researcher used test to collect the data. While for qualitative method, it was analyzed by using questionnaire and observation. The test is used by the researcher to measure student’s listening skill improvement. In each cycle the researcher conducted pre-test and post-test. The questionnaires were used to support the data. Observation was used to evaluate the learning processes. The results show that the use of video in teaching listening was success to improve students’ achievement. It can be seen from the result of each test in each cycle. In cycle 1 the mean scores of pre-test 1 was 53.06, post-test 1 was57.83. While in cycle 2, pre-test 2 was 71.94, post-test 2 was 75.81. The result of questionnaires shows that the students could understand the content of the video easily. The result of observation showed that video could create fun learning. Keywords: listening, video, teaching listening, teaching listening through video